The vanitative motive and its reflection in T. Shevchenko’s poetry - Кулікова, Оксана Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The peculiarity of the baroque “vanity of the vanities” motive use in the creative activity of T. Shevchenko has been observed in the article. It has been proved in the article, that in the poet’s creative activity, there are a lot of common with the baroque literature things, and the thoughts about the transient human life and its significance in the course of eternity make up almost inalienable part of the creative inheritance of  T. Shevchenko. This generality with the baroque themes lies in the fact that in the course of this theme development, Shevchenko uses both the Bible imagery and appeals to traditions of the baroque poetry.